HUBUNGAN KONTROL DIRI DAN HARGA DIRI TERHADAP KECENDERUNGAN NARSISTIK PADA MAHASISWA SEMESTER AWAL PENGGUNA INSTAGRAM - Aulia Nur Laeli; Elsa Sartika; Furqan Nugraha Rahman; Rifka Fatchurrahmi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2018)
This study aims to determine relationship between self-control and self-esteem with a narcissistic tendency in the first semester students on instagram users. Subjects were students of the Faculty of Psychology second grade with characteristics aged 18-21 years, using social media instagram and upload photos or videos as much as more than 5 times a day. The results were analyzed using regression multiple analysis. Based on result of data analysis were correlation coefficient between self-control variable and self-esteem with narcissistic tendency score R = 0.535, with significance value equal to p = 0.000 (p <0.01), and F value count on anova table equal to 10.040 (F count> F table = 4.74). The effective contribution of self-control and self-esteem to the narcissistic tendency of 28.7%, while the remaining 71.3% is influenced by other variables. There is a negative relationship between self-control and self-esteem with the tendency of narcissistic in the first semester students instagram users. The higher the self-control and self-esteem the lower the narcissistic tendency.